Aortic Wall Elastic Properties in Case of Bicuspid Aortic Valve - Goudot, Guillaume; Mirault, Tristan; Bruneval, Patrick; Soulat, Gilles; Pernot, Mathieu; Messas, Emmanuel (Frontiers in Physiology, 2019)
Purpose of the review Bicuspid aortic valve (BAV) is associated with a significant risk of development of aneurysm and dissection of the ascending thoracic aorta. Development of what is called BAV associated aortopathy is particularly heterogeneous with an uncertain prognosis and with no prognostic biomarkers except for the aortic diameter. This situation leads to an important variability of the therapeutic strategy of this aortopathy. By reviewing the literature on aortic stiffness in case of BAV, we aimed at evaluating its potential prognostic role in the development of aortic dilatation. Recent findings Studies evaluating aortic stiffness, with ultrasound or magnetic resonance imaging, converge towards the description of an increased segmental aortic stiffness in BAV patients regardless of age, diameter or aortic level, from the root to the arch. Even though there is a lack of longitudinal studies evaluating the progression of aortic dilatation, new data have recently shown the potential prognostic role of the maximal rate of systolic distension of the aortic wall with magnetic resonance imaging. Summary Although the use of aortic distensibility calculation is a simple evaluation of stiffness that could be easily transposed in daily practice, its interpretation remains uncertain. New arterial stiffening indicators seems more promising but need a stronger validation.